2020
DOI: 10.1177/0149206320936335
|View full text |Cite
|
Sign up to set email alerts
|

Welcome Back? Job Performance and Turnover of Boomerang Employees Compared to Internal and External Hires

Abstract: “Boomerang” employees are workers who leave an organization and are later rehired by that same organization. Although many organizations rehire former employees, only a handful of studies have examined this phenomenon. The present study uses a large, longitudinal data set to examine the performance and turnover of boomerang employees rehired into management positions (n = 1,318). Further, we provide some of the first comparisons between boomerang employees and two traditional sources of employees: external hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Despite the popular perception among HR and recruitment professionals that boomerangs should outperform other employees in general (c.f. Apy & Ryckman, 2014; Brin, 2018; Flesher, 2017; Grensing‐Pophal, 2020; HR Exchange, 2019; Nelson, 2016), our null performance findings between boomerangs and internal hires are consistent with findings from retail (Arnold et al, in press) and healthcare settings (Keller et al, in press). In addition, when Swider et al (2017) compared boomerang athletes to a narrow subset of stayers with similar career timelines, they also found that boomerangs did not perform as well as the stayers.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Despite the popular perception among HR and recruitment professionals that boomerangs should outperform other employees in general (c.f. Apy & Ryckman, 2014; Brin, 2018; Flesher, 2017; Grensing‐Pophal, 2020; HR Exchange, 2019; Nelson, 2016), our null performance findings between boomerangs and internal hires are consistent with findings from retail (Arnold et al, in press) and healthcare settings (Keller et al, in press). In addition, when Swider et al (2017) compared boomerang athletes to a narrow subset of stayers with similar career timelines, they also found that boomerangs did not perform as well as the stayers.…”
Section: Discussionsupporting
confidence: 80%
“…Building on the definition presented in Shipp, Furst‐Holloway, Harris, and Rosen (2014), we define boomerangs as returning employees who terminated their employment voluntarily or involuntarily, and who left for employment (e.g., a new position at a competing firm, career change, or self‐employment) or non‐employment reasons (e.g., education, parenting) (see also Arnold et al, in press, Figure 1). Excluded from this definition are interns, seasonal workers, those returning from furlough or temporary leave, or who transferred to a new location.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 3 more Smart Citations